The Professional Ethic Values Promoted by Governing Documents of a Public University in Mexico - Osuna Lever, Cecilia; Luna Serrano, Edna (Education Policy Analysis Archives, 2008)
This study analyses the professional-ethic values promoted by education policy in public university education in Mexico, the semantic correspondence of said policy with programs, and the strategies for its implementation. Following the methodology of textual analysis, we reviewed the National Programs of Education, documents that embed the academic plan at the Universidad Autónoma de Baja California, and the curricula of licenciaturas in the areas of natural science and engineering and technology. It was identified that the core elements of university education are social compromise, professional competence, and education in values. Our findings indicate that there is textual correspondence among the most relevant categories of the documents; however, it is worth pointing out the absence of strategies that explicitly promote student development of professional-ethic values.